Target Organ Damage in Hypertension in an Academic Hospital (TAJ: Journal of Teachers Association, 2009)
One hundred hypertensive patients were selected randomly from medicine indoor; 66 were males, 34 were females. Age ranges were 20 to 70+ years. Detail history was taken, comprehensive physical examination and relevant investigations were done to detect various target organ damage. These findings were correlated with age, sex, occupation, socioeconomic status, duration of hypertension, drug compliance and other risk factors of cardiovascular disease. Incidence of TOD were as follows: 65.15% of males and 52.94% of females developed stroke; 70% of total patients developed some forms of cardiac complications, 14% had left ventricular failure, 43.93% of males had left ventricular hypertrophy (LVH) 26.47% of females had LVH; 27% of patients had renal complications; 23% of patients had retinopathies; 6% of patients had malignant hypertension; 20% of patients had peripheral vascular disease.   doi: 10.3329/taj.v21i1.3222 TAJ 2008; 21(1): 63-68